COMPARATIVE ANALYSIS OF MULTIPLE CRITERIA DECISION MAKING (MCDM) APPROACH IN WAREHOUSE LOCATION SELECTION OF AGRICULTURAL PRODUCTS IN THAILAND - Khaengkhan, Martusorn; Hotrawisaya, Chattrarat; Kiranantawat, Bhuk; Shaharudin, Mohd Rizaimy (International Journal of Supply Chain Management, 2019)
The objective of this study was to select the suitable warehouse location, which is the focus for business organisations that buy, produce, and store the agricultural products of grass flowers, by using the Multiple Criteria Decision Making theory (MCDM). Three methods were used, which were the Simple Additive Weighting (SAW), Analytic Hierarchy Process (AHP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Seven main factors that influence the selection of an agricultural product warehouse were explored - the size of the area, land price, labour cost, utilities, the quantity of raw materials in the area, ease of access to the place, and distance from the source of the raw materials to the location. Five areas for the warehouse Chiang Rai province, Thailand were compared to ascertain the suitability of warehouse location by using these factors. The results show that Pa Sang Sub-district, Mae Chan District (E) was the most suitable for the agricultural product warehouse. This study can be further applied to decision making in agricultural businesses.